Decision Support System For The Determination Of Field Work Practice Results In Students Using The Moora Method (Case Study : Pt. Telekomunikasi Binjai) - Novriansyah (Yayasan Kita Menulis, 2022)
PT. Telekomunikasi Indonesia Binjai Branch is an information and communication company as well as a complete telecommunications service and network provider in Indonesia. Acceptance of students to carry out Field Work Practices (PKL) is one of the important goals for companies to introduce the world of telecommunications in Binjai City. Street vendors are student activities directly in professional work activities at an institution, company or institution within a certain period of time in accordance with the curriculum. And to overcome these problems we need a method that can predict the number of new installations. After carrying out the Field Work Practice (PKL) in the company, students are entitled to get the results of the activities that have been carried out during the PKL. The number of students who carry out PKL in the company makes it difficult for office employees to provide PKL results from each of the existing students. Based on the results of research that has been done at PT. Telekomunikasi Indonesia Binjai Branch, the process of assigning value to the results of street vendors activities is done manually. In this study a Decision Support System (DSS) will be built using the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) method which is a method that has a calculation with a minimum and very simple calculation. The system is designed with the PHP programming language and MySQL database, after processing the 15 inputted data, it is found that A15 (Wiratana Sanjaya) is in the first rank. With these results it was also concluded that A15 became a student with the best Field Work Practice results at PT. Telekomunikasi Indonesia Binjai Branch.